Metaphrase: An Aid to the Clinical Conceptualization and Formalization of Patient Problems in Healthcare Enterprises - Tuttle, M. S.; Olson, N. E.; Keck, K. D.; Cole, W. G.; Erlbaum, M. S.; Sherertz, D. D.; Chute, C. G.; Elkin, P. L.; Atkin, G. E.; Kaihoi, B. H.; Safran, C.; Rind, D.; Law, V. (Methods of Information in Medicine, 1998)
Patient descriptors, or “problems,” such as “brain metastases of melanoma” are an effective way for caregivers to describe patients. But most problems, e.g., “cubital tunnel syndrome” or “ulnar nerve compression,” found in problem lists in an Electronic Medical Record (EMR) are not comparable computationally – in general, a computer cannot determine whether they describe the same or a related problem, or whether the user would have preferred “ulnar nerve compression syndrome.” Metaphrase is a scalable, middleware component designed to be accessed from problemmanager applications in EMR systems. In response to caregivers' informal descriptors it suggests potentially equivalent, authoritative, and more formally comparable descriptors. Metaphrase contains a clinical subset of the 1997 UMLS Metathesaurus and some 10,000 “problems” from the Mayo Clinic and Harvard Beth Israel Hospital. Word and term completion, spelling correction, and semantic navigation, all combine to ease the burden of problem conceptualization, entry and formalization.
Keywords: Computer-based Patient Records; Problem Lists; Formalization; Unified Medical Language System; Semantic Navigation